2010
DOI: 10.1111/j.1471-0307.2009.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of proteinaceous antifungal substances from Lactobacillus brevis NCDC 02

Abstract: Forty standard Lactobacillus cultures were checked for their antifungal properties against nine standard fungi. Yeasts were found to be more resistant than moulds. Lactobacillus brevis NCDC 02 was selected for further studies due to the maximum antifungal activity and proteinaceous nature of antifungal substance production. The optimum production of antifungal substances was at 37°C for 48 h and at the initial pH of 6-7 of the medium. The antifungal substances were heat-and pH-stable. The antifungal substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…According to the analysis above all, we concluded that the compound produced by L. plantarum IMAU10116 may be a peptide. This was similar to other reports (Magnusson and Schnurer 2001; Falguni et al. 2010) that identified the production of antifungal proteinaceous compounds by Lactobacillus .…”
Section: Discussionsupporting
confidence: 92%
“…According to the analysis above all, we concluded that the compound produced by L. plantarum IMAU10116 may be a peptide. This was similar to other reports (Magnusson and Schnurer 2001; Falguni et al. 2010) that identified the production of antifungal proteinaceous compounds by Lactobacillus .…”
Section: Discussionsupporting
confidence: 92%
“…When the selected LbBio2 was separated by ultrafiltration to deeper investigate the possible presence of other active metabolite other than organic acids, interestingly the activity was retained in the fraction containing molecules with size higher than 30 kDa. These results suggested that the antifungal activity observed in LbBio2 could be attributed to the pool of metabolites produced by the L. brevis strain including proteinaceous compounds in agreement with other authors (Corsetti et al, 1998;Niku-Paavola et al, 1999;Ryan et al, 2011;Gerez et al, 2013;Atassanova et al, 2003;Falguni et al, 2010). In particular, Falguni et al (2010) selected a L. brevis strain for its antifungal activity and they demonstrated the proteinaceus nature of the active substances and their molecular weight ranged from 1 kDa to 5 kDa.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggested that the antifungal activity observed in LbBio2 could be attributed to the pool of metabolites produced by the L. brevis strain including proteinaceous compounds in agreement with other authors (Corsetti et al, 1998;Niku-Paavola et al, 1999;Ryan et al, 2011;Gerez et al, 2013;Atassanova et al, 2003;Falguni et al, 2010). In particular, Falguni et al (2010) selected a L. brevis strain for its antifungal activity and they demonstrated the proteinaceus nature of the active substances and their molecular weight ranged from 1 kDa to 5 kDa. Actually, the involvement of small peptides in the inhibition of mould growth has been widely demonstrated (Schnürer and Magnusson, 2005) while there are few evidences on the role of larger protein compounds in the antifungal activity of LAB.…”
Section: Discussionsupporting
confidence: 88%
“…by L. brevis [26,27]. Only a few papers report a broad spectrum of inhibitory effects of LAB against micromycetes [15,16,28].…”
Section: Resultsmentioning
confidence: 99%